Factors contributing to individual capacity building levels among women entrepreneurs - Muhamad Nasharudin, Nurfazreen Aina; Redzuan, Ma’rof; Abdul Rahman, Abdul Razak (Universiti Putra Malaysia Press, 2013)
This research was conducted to identify factors which contribute to individual capacity building levels among women entrepreneurs. For this purpose, the study was carried out in the states of Johor and Melaka which involved 200 women entrepreneurs who made up the respondents of this particular research. This study was done through survey method using questionnaires. Simple Random Sampling methodology was used to gather the necessary data. The data were analyzed by means of 'Statistical Package for Social Science' (SPSS). Results of the Stepwise Regression test revealed that education level contributed the most towards individual capacity building levels among women entrepreneurs, with a variance of 51.9%. This finding indicates that education level can influence the capability and credibility of an individual towards achieving progress in her business.